Analyzing the Performance Trends in Licensure Examination for Teachers (LET) Among Bachelor of Elementary Education (BEEd) Graduates: A Quantitative Approach - Salendab, Fahad A.; Dela Cruz, Jesaly E.; Tabifranca, Crizelle A.; Fortaliza, Jonipol E. (Future Science / FSH-PH Publications, 2024)
The study analyzes the performance trends in the Licensure Examination for Teachers (LET) among Bachelor of Elementary Education (BEEd) graduates from Sultan Kudarat State University – Kalamansig Campus from 2018 to 2023. A descriptive-comparative research design was employed to statistically measure the objectives of the study. Data were obtained from the Professional Regulation Commission (PRC). The study’s respondents are 73 first-timers and 112 repeaters. A total of 185 BEEd examinees were the respondents of the study. Also, the study utilized frequency and percentage counts, z-scores, and p-values to compare the performance and test for significant differences. The results revealed that the performance trends among the BEEd graduates was fluctuating. Performance of first-timers are higher than repeaters in most periods, with institutional passing rates below national passing rates. Notably, exceptional performances were recorded during the March 2019, June 2022, and October 2022 examination periods, where institutional passing rates surpassed national passing rates. The study identifies several factors influencing LET performance, including academic preparation, review sessions, and external disruptions such as the COVID-19 pandemic, which impacted the consistency and preparation of examinees. The data suggest that while first-timers showed relatively strong performance, repeaters faced significant challenges, underscoring the need for targeted support systems to enhance their preparedness and outcomes. The findings highlight the critical importance of continuous monitoring and strategic interventions to improve LET performance. Implementing effective support mechanisms for repeaters, improving academic and review processes, and addressing external factors are essential steps toward enhancing the quality of teacher education.